The Influence of Corporate Social and Environmental Responsibility and Information Technology Investment on Company Value with Corporate Innovation as a Moderation - Keristina, Ni Made Deni; Adiputra, I Made Pradana; Sujana, Edy (Advances In Social Humanities Research, 2024)
This research aims to determine the influence of several variables, namely (1) CSER and (2) IT investment, on company value, which is moderated by the company innovation variable in mining sector companies listed on the BEI in 2018 - 2022. The population in this study is all mining companies, as many as 76 companies. Sampling used purposive sampling with certain criteria and obtained a sample of 9 companies multiplied by five years of observation to become 45 financial reports. The data collection technique used is a documentation study that analyses the financial reports of mining companies that meet the sample criteria according to the needs of the data to be processed. Data were analysed using the STATA application. The research results found that CSER and IT investment had no effect on company value; company innovation was not able to strengthen the influence of CSER on company value, while company innovation was able to strengthen the effect of IT investment on company value. This research was also conducted on mining companies, considering that the mining sector is closely related to the environment. According to the data previously presented, the value of companies in the mining sector experiences fluctuations, which decrease more frequently each year.